Loss of naive T lymphocytes is associated with advanced liver fibrosis in alcohol use disorder. (1st August 2020) - Zuluaga, Paola; Sanvisens, Arantza; Teniente-Serra, Aina; El Ars, Oumaima; Fuster, Daniel; Quirant-Sánchez, Bibiana; Martínez-Cáceres, Eva; Muga, Roberto
Highlights: Phenotype of T lymphocytes in AUD patients is similar to that described in immunosenescence. AUD patients exhibit an expansion of CD8 TEMRA cells and a trend towar Th2 immune response. AUD patients with advanced liver fibrosis have reduced populations of naïve T cells. AUD patients with advanced liver fibrosis have larger populations of CD4+ memory T cells. Abstract: Background: Alcohol use disorder (AUD) is associated with changes in cellular immunity. The objective of the present study was to analyze the contribution of AUD to the differentiation of T cells and associations with advanced liver fibrosis (ALF). Methods: This cross-sectional study included patients admitted for treatment of AUD between 2013 and 2016. T cell immune-phenotyping defined four profiles of cellular differentiation according to the expression of CCR7 and CD45RA: naive T cells, central memory (TCM ) cells, effector memory (TEM ) cells, and terminal effector (TEMRA ) cells. CD4 + memory cells were subdivided into Th1, Th2, and Th17 according to the expression of CXCR3 and CCR6. The stages of cellular differentiation were compared to healthy controls. ALF was defined as FIB-4 > 3.25. Results: Seventy-nine patients (81% men) with a median age of 50 years (IQR: 45−56 years) and median ethanol consumption of 150 g/day (IQR: 100−200 g/day) were included in the study. Compared to healthy controls, patients with AUD had fewer CD4 + naive cells (p < 0.001), more TCM and TEM cells ( p = 0.003 and p = 0.050, respectively), and larger Th2 populations ( p = 0.03 ). Among CD8 + cells, the percentage of TCM, TEM, and TEMRA were higher in patients with AUD than in the healthy controls ( p < 0.05 ). Patients with ALF had fewer CD4 + and CD8 + naive cells (p < 0.05) and more CD4 + memory cells than patients without ALF. Conclusions: Altered lymphocyte differentiation in AUD patients suggests immunosenescence. An increase in memory cells and decrease in naive cells is associated with ALF.